Gravity-driven wet granular free-surface flows down an inclined plane: Effects of the inclination angle - Vo, Thanh-Trung; Nguyen, Trung-Kien; Nguyen, Cuong T. (Vietnam Journal of Mechanics, 2022)
Wet granular materials flowing down an inclined plane are omnipresent in multi-field engineering. Although extensive research has been carried out to investigate the flowability of such flows, our understanding of the flows like landslides is limited due to the presence of the cohesive forces between particles and the arbitrarity of inclination angle. In this paper, we explore the effects of the inclination angle on the velocity profiles and force distribution of the gravity-driven wet granular free-surface flows in the steady-flowing state by means of an extensive discrete element method with the inclusion of the capillary cohesion law. This capillary cohesion law is enhanced by the capillary attraction force due to the presence of the liquid bridges between near-neighboring particles. The results show that the mobility of wet granular materials is strongly controlled by the inclination angle due to the domination of the gravity effects of particles as compared to the cohesion effects and rough effects of the inclined surface. These observations are consistent with the previous experimental work done on the granular collapse on an inclined plane. Furthermore, in its steady-state flow, the granular materials separate stably into two different flowing regions: solid-like and fluid-like flows, and the depth of these flows strongly depends on the values of the inclination angle. More interestingly, the inclination angle also strongly governs the density and intensity of the tensile and compressive components of the normal forces and tangential forces in both solid-like and fluid-like regions with different characteristics.